Surgical Instrument Optimization to Reduce Instrument Processing and Operating Room Setup Time. (February 2020) - Crosby, Lauren; Lortie, Eric; Rotenberg, Brian; Sowerby, Leigh
Objective: As health care expenditures rise, novel ways to increase efficiency are sought. The operating room (OR) represents an area where there is opportunity to optimize work flow and supply use. Evidence suggests that instrument redundancy in the OR tends to be high and that direct cost savings can be achieved by "optimizing" surgical trays. The purpose of this study was to quantify the potential time savings associated with surgical tray optimization. Methods: Instrument utilization was reviewed for 4 procedures: tonsillectomy, sinus surgery, septoplasty, and septorhinoplasty. Instruments used in <20% of cases were excluded. Data on tray assembly time in the central processing department and instrument setup time in the OR were prospectively collected over a 3-month period before and after tray optimization. Student's t test (α = 0.05) was used to determine whether times were significantly different following optimization. Results: Tray assembly times were found to be significantly shorter following optimization, with percentage reduction in time ranging from 58% to 66% ( P < .05). In the OR, percentage reduction in setup time ranged from 26% to 37% ( P < .05). Variability in assembly and setup times was also found to be narrower postoptimization. Discussion: Tray optimization may reduce stress and adverse events and allow managers to better estimate staffing requirements. Cost-benefits could not be determined given a limited understanding of how departments choose to redistribute time savings. Implications for Practice: Measurable and significant time savings can be achieved by assessing instrument utilization rates and reducing tray redundancy, leading to lower performance variability and improved efficiency.